dukungan Dukungan Keluarga Terhadap Tingkat Kecemasan Pada Pasien Tumor Payudara - Nurpadila Dila Nurpadila (Jurnal Kesehatan Marendeng, 2021)
Patients with breast tumors need support from their families because family support is very influential on mental in the form of enthusiasm, empathy, trust, attention so that family members who are in a condition experiencing breast tumors see that the family is always supportive and ready to provide help and assistance if needed. The study was conducted in the surgical poly room of the Majene Regency General Hospital in 2017. The research objective was identified "The relationship between cholesterol levels and stroke in outpatients at the Majene Regency Hospital in 2017" The type of research carried out was an analytical survey using a cross sectional research design to collect data systematically. cross sectional Chi-Square statistical test. The results of the Chi-Square analysis showed a significance value of p = 0.003 (p < 0.05), which means that there is a relationship between family support and anxiety in breast tumor patients in the surgical ward of the Majene District Hospital in 2017. can provide health education to patients so that it can be useful to reduce patient anxiety due to hospitalization